THE CASE OF SURGICAL TREATMENT OF A CHILD WITH A DOUBLING OF THE ILEUM - A. E. Gaydayenko; I. V. Kirgizov; A. G. Talalaev; K. N. Baranov; I. A. Shishkin; A. A. Gusev (Педиатрическая фармакология)
This clinical observation was carried out over a teenager at age 17 with long lasting doubling of the ileum, formation of sinus openings in the lumen of the intestine, exhibited by recurrent intestinal bleeding and abdominal pain. Surgery was the only way to effectively treat the child. The indications for surgery were the clinical manifestations of chronic invagination resistant to conservative treatment.